If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + -2(7x + -13) = -29 Reorder the terms: 3x + -2(-13 + 7x) = -29 3x + (-13 * -2 + 7x * -2) = -29 3x + (26 + -14x) = -29 Reorder the terms: 26 + 3x + -14x = -29 Combine like terms: 3x + -14x = -11x 26 + -11x = -29 Solving 26 + -11x = -29 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-26' to each side of the equation. 26 + -26 + -11x = -29 + -26 Combine like terms: 26 + -26 = 0 0 + -11x = -29 + -26 -11x = -29 + -26 Combine like terms: -29 + -26 = -55 -11x = -55 Divide each side by '-11'. x = 5 Simplifying x = 5
| 6x8/13 | | -(5-x)=2x+3 | | 44=7x-3(5x+4) | | -5+(-12)*(-2)/8 | | 9x+48y=6fory | | 36y^6x^7+30y^7x^4/6x^3y^4 | | 4=1-n-3 | | -14=-5a+3a | | -2(2x-7)+4=-4x+18 | | n+6n=-7 | | m-2-5=-1 | | 117=-9k | | x/5-12=-6 | | (x-6)(x-1)=-x-2 | | 72-2x=7x-18 | | n/19=9 | | 2(4x^2+x)=0 | | 6b-b=-15 | | 4x-(3x)=7(x-3)+10 | | 17+3y-4=13y-11-4y | | 1/6(5x-2)=3 | | 8/3x+1/3x=3x+25/3+5/3x | | x+89=2x+24 | | 4x-7+2x=-24-1 | | x^4+sqrt(17)x^2-17=0 | | X^2+2.5x-1.5=0 | | 8c+5c=2+4 | | x/3=44 | | 11-2x(7-2x)=45 | | B+2+b-6= | | 220=-20x | | 8x(2+3q)= |